UKRAINIAN NATIONAL IDEA IN THE WORKS OF MARKO CHEREMSHYNA - Stefyuk (Oleshuk), I. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
According to Vasyl Stefanyk, from the soul of Ivan Semanyuk (Markо Cheremshyna) "two corridors came out" – his public and literary and lyrical hypostases, which did not intersect. However, in the course of the interpretation of the topic we have defined – "Ukrainian national idea in the work of Marko Cheremshyna" – a clear relationship can be traced with the socio-political heart of the worldview of Ivan Semanyuk , doctor of law, lawyer and public figure. After all, to a large extent, his own visions of nation-building formed the basis of painting the image of the state leader. The purpose ofour research is to find out how the writerly and socio-political hypostases of Yvan Semanyuk (Marko Cheremshyna) were correlated and to analyze which of the nation-building accents outlined by the writer resonate with the present. The relevance of the work lies in the fact that the chronotopic panorama of Marko Cheremshyna's text is considered for the first time through the prism of nation-centric vectors. In addition, in the conditions of the Russian-Ukrainian war, the research is not so much the subject of the image – i.e. the artistic and memoir heritage of Marko Cheremshyna itself – because history repeats itself again. Two works by Marko Cheremshyna are separately characterized, which for ideological reasons were either banned from publication at all (the fairy tale "Bird of Paradise"), or were published with fragments and were not considered among his full-fledged works ("Jordan").